Weed-control efficiency of different herbicides in rainfed groundnut (Arachis hypogaea) - PATEL, S R; LAL, NAGESHWAR; THAKUR, D S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the rainy season of 1994 and 1995 at Raigarh to study the efficiency of different herbicides in rainfed groundnut (Arachis hypogaea L.). The herbicides wereÂ applied as pre-planting incorporation, pre-emergence to control annual weeds especially coxcomb (Celosia argentea L.). The major weed species observed in the field were coxcomb, barnyard grass (Echinochloa crus-galli(L.) Beauv.],jungle rice (Echinochloa colona (L.)Link], bermuda grass[Cynodon dactylon (L.)Pers.] and purple nutsedge (Cyperus rotundus L.) in decreasing order. Oxyfluorfen @ 0.4 kg ai/ha as pre-emergence showed maximum weed-control efficiency, particularly for coxcomb and minimum weed index (92.3 and 13.2% respectively) but lagged behind the control (Weed-free plot)in pod yield. The pod yield under the control and oxyfluorfen was 1 561 and 1 361 kg/ha respectively. Lactofen @ 0.15 kg ai/ha applied as post-emergence recorded weed-control efficiency of 53.2, but was inferior in pod yield to pendimethalin @ 1.5 KG ai/ha as pre-emergence and fluchlorlin @ 1.0 kg ai/ha as pre-planting incorporation, which recorded 1 182, 1327 and 1 314 kg/ha pod yield respectively.